2015
DOI: 10.1371/journal.pone.0139923
|View full text |Cite
|
Sign up to set email alerts
|

Gait Biomechanics and Patient-Reported Function as Predictors of Response to a Hip Strengthening Exercise Intervention in Patients with Knee Osteoarthritis

Abstract: ObjectiveMuscle strengthening exercises have been shown to improve pain and function in adults with mild-to-moderate knee osteoarthritis, but individual response rates can vary greatly. Predicting individuals who respond and those who do not is important in developing a more efficient and effective model of care for knee osteoarthritis (OA). Therefore, the purpose of this study was to use pre-intervention gait kinematics and patient-reported outcome measures to predict post-intervention response to a 6-week hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
32
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 61 publications
8
32
0
1
Order By: Relevance
“…Despite the use of 10fold cross-validation of the training dataset to attempt to improve generalizability of classification, the model slightly overfit to the training dataset as there was lower classification accuracy for the independent testing dataset compared to the 10-fold crossvalidation of the training dataset. Regarding real-world usability, previous studies that have classified IMU-generated running and walking patterns have consistently reported classification accuracy greater than 80% (Kobsar et al, 2014(Kobsar et al, , 2015Phinyomark et al, 2014;Ahamed et al, 2018Ahamed et al, , 2019Benson et al, 2018b;Clermont et al, 2018). Thus, the reported 93.17% accuracy for the training dataset and 83.81% accuracy for the independent testing dataset in the current study suggests that this classification mechanism has practical use.…”
Section: Discussionsupporting
confidence: 56%
“…Despite the use of 10fold cross-validation of the training dataset to attempt to improve generalizability of classification, the model slightly overfit to the training dataset as there was lower classification accuracy for the independent testing dataset compared to the 10-fold crossvalidation of the training dataset. Regarding real-world usability, previous studies that have classified IMU-generated running and walking patterns have consistently reported classification accuracy greater than 80% (Kobsar et al, 2014(Kobsar et al, , 2015Phinyomark et al, 2014;Ahamed et al, 2018Ahamed et al, , 2019Benson et al, 2018b;Clermont et al, 2018). Thus, the reported 93.17% accuracy for the training dataset and 83.81% accuracy for the independent testing dataset in the current study suggests that this classification mechanism has practical use.…”
Section: Discussionsupporting
confidence: 56%
“…Frontal plane kinematics of the knee and hip have been identified in research surrounding the aetiology of knee osteoarthritis (OA) and the difference in prevalence between males and females (Phinyomark, Osis, Hettinga, Kobsar, & Ferber, 2016). Again working with a sample of individuals with knee OA, research has shown difference in hip frontal plane kinematics between those that were classified as high-responders to treatment as compared to those that were grouped into the low-or non-responder category (Kobsar, Osis, Hettinga, & Ferber, 2015). The potential to predict with high accuracy whether a patient will respond well to a specific treatment has meaningful implications for clinical practice by saving time and resources.…”
Section: Clinical and Research Applicationsmentioning
confidence: 99%
“…There is no cure for OA; current nonsurgical management guidelines recommend exercise, weight management, and biomechanical interventions to reduce symptoms and preserve function . Although it is well accepted that exercise therapy leads to improvements in pain, physical function, and quality of life, the reported treatment success varies, possibly because of variances in therapy intensity or dosage and substantial heterogeneity in disease severity, age, body mass index (BMI), and pre‐intervention movement mechanics and activity levels . Identifying characteristics that enhance or diminish treatment response would facilitate a more tailored approach to exercise intervention and optimize efficacy and minimize adverse events.…”
Section: Introductionmentioning
confidence: 99%